(untitled) (European Journal of Transport and Infrastructure Research, 2008)
EJTIR keeps track of download-statistics for each issue, to be published in the next issue. Specifically we will publish, for each paper and book review, how many times the paper’s pdf-file has been downloaded during the time that the issue it belongs to was EJTIR’s frontissue. In addition, we show the average number of downloads per week.